ANALISIS STRATEGI BISNIS KUMIS KUCING KERING PT POROS NUSANTARA UTAMA JAWA BARAT - Wiranthi, Puspi Eko; Firmansyah, Iman (Forum Agribisnis, 2012)
Poros Nusantara Utama Ltd (PT PNU) is one of the companies that sell herbal products. The company has partnership agreement with local farmers group of Gede Pangrango and Halimun Salak National Parks. In 2009, the company received organic certification for dried kidney tea/java tea (Ortoshiphon stamineus) though it has no effect to its trade. The purposes of the research are: 1) to identify internal and external factors of PT PNU, 2) to formulate marketing strategy for dried java tea, 3) to compose the priority of marketing strategies. The methods are IE, SWOT and QSP. IE matrix shows PT PNU is on hold and maintain where the strategies are market penetration and product development. SWOT matrix shows eight strategies where based on QSP, the first priority is to maintain product quality.